Kinetic Modeling and Effect of Process Parameters on Selenium Removal Using Strong Acid Resin - Rajamohan, N.; Rajesh Kannan, R.; Rajasimman, M. (Engineering, Technology & Applied Science Research, 2016)
Heavy metal pollution due to the contamination of Selenium above the tolerable limit in the natural environment is a challenging issue that environmental scientists face. This study is aimed at identifying ion exchange technology as a feasible solution to remove selenium ions using 001x7 resin. Parametric experiments were conducted to identify the optimal pH, sorbent dose and speed of agitation. Selenium removal efficiency of 85% was attained at pH 5.0 with 100 mg/L selenium concentration. The increase in resin dose was found to increase removal efficiency. However, metal uptake decreased. The experiments on the effect of concentration proved the negative effect of higher concentrations of selenium on removal efficiency. The ion exchange process was proved to be optimal at an agitation speed of 200 rpm and a temperature of 35 °C. Pseudo second order model was found to fit the kinetic data very well compared to the pseudo-first order model and the pseudo second order rate constant was estimated as 8.725x10-5 g mg-1 min-1 with a solution containing 100 mg/L selenium.